Participação Infantil: experiência de pesquisa realizada em organização social na Zona Oeste do Rio de Janeiro - Goulart, Angélica Moura (2009)
This report proposes itself to be one string in the web of reflections that weave the debate about childish participation, starting with the cooperation between children and adults. Its web is composed by distinct and autonomous fields - childhood, social laws and participationthat intersect themselves in the ambit of one investigation accomplished at one social organization - Fundação Xuxa Meneghel- that has as a center pivot of its actions the promotion and protection of children and adolescents who live in a vulnerably social situation in West Zone of Rio de Janeiro. This project is about a micro-experience that searches to comprehend the child being related to his human and social rights by his influence in the social practices that exist in our culture. The right to childhood participation- toll to selfprotection and promotion of children as full citizens exercising their citizenship-materializes itself in an investigation in which the convectional methodologies conceptions begin to reconstruct themselves by the childish voice that dialogue with each other and the adults. The children present their points of view and the meanings that they attribute to their environment and to their possibilities and limits to participate in an authentic way in their primary socializing instances: the family, the school and the community. The experience constitutes in a provocation in the view to the culture and identity of these children who participate in the project, their experiences expressed by representation of actions and emotions contextualized in time and space, in an attempt do compose with them, - and amplifying to all the children at the Institution - a comprehension of the right to participate, teach and learn in a social and cultural perspective.